Phase II study of carboplatin, pemetrexed, and bevacizumab in advanced nonsquamous non–small‐cell lung cancer - Nicole F. Laslett; SuJung Park; Gregory A. Masters; David D. Biggs; Charles J. Schneider; Jamal G. Misleh; Kathir Suppiah; Pamela S. Simpson; Stephen Grubbs; Timothy F. Wozniak; Michael Guarino (Cancer Medicine, 2018)
Abstract Lung cancer remains the leading cause of cancer death throughout the world. Despite new chemotherapeutic, immunomodulating and molecularly targeted agents, patients with locally advanced or metastatic disease still have a poor prognosis. This trial looked to combine antiangiogenic therapy with a first‐line cytotoxic chemotherapy doublet, hoping to extend median progression‐free survival (PFS) while minimizing toxicity in patients with advanced nonsquamous non–small‐cell lung cancer (NSCLC). In this single institution, single‐arm study, 51 patients (age >18 yo) were followed from 2007 to 2012. Patients with stage IV nonsquamous NSCLC and patients with recurrent unresectable disease (nonradiation candidates) were eligible. Treatment consisted of carboplatin AUC 5 IV 30‐60 minutes, pemetrexed 500/mg2 IV 10 minutes, bevacizumab 15 mg/kg IV (90 minutes 1st dose, 60 minutes 2nd dose, 30 minutes subsequent doses). Treatment was administered every 21 days and planned for 6 cycles, in the absence of disease progression or unacceptable toxicities. Growth factor support was not permitted prophylactically but allowed for toxicities, as were dose reductions. Maintenance treatment for those with stable disease or better consisted of Bevacizumab 15 mg/kg every 3 weeks for up to 1 year. Between November 2007 and March 2012, 51 patients were followed in the phase II trial of carboplatin, pemetrexed, and bevacizumab. Patients were enrolled over a 24‐month period. After the end of treatment visits, subjects were followed at least every 3 months for survival data. The median follow‐up period was 49 weeks (6 weeks to 178), and the median number of treatment cycles was 6 (range, 1‐6). Among the 50 patients assessable for response, median overall survival was 49 weeks (95% CI, 0‐62.7) with median PFS of 28 weeks (95% CI, 0‐132.4). A complete or partial response was seen in 28 (59.5%) patients. Grade 3‐4 treatment‐related adverse events occurred in 9 (17.6%) of 51 patients; the most common were thrombocytopenia (4 [7.8%]) and neutropenia (3 [5.9%]). Three (5.8%) of 51 patients were discontinued because of treatment‐related adverse events (grade 3 diarrhea, thrombocytopenia, dehydration, fatigue, and grade 4 respiratory distress), and 1 patient (1.9%) was found to be ineligible due to anticoagulation use. A novel 3‐drug combination for advanced nonsquamous NSCLC shows promising efficacy with modest toxicity.